Human Beta Cell Regenerative Drug Therapy for Diabetes: Past Achievements and Future Challenges - Wang, Peng; Karakose, Esra; Choleva, Lauryn; Kumar, Kunal; DeVita, Robert J.; Garcia-Ocaña, Adolfo; Stewart, Andrew F. (Frontiers in Endocrinology, 2021)
A quantitative deficiency of normally functioning insulin-producing pancreatic beta cells is a major contributor to all common forms of diabetes. This is the underlying premise for attempts to replace beta cells in people with diabetes by pancreas transplantation, pancreatic islet transplantation, and transplantation of beta cells or pancreatic islets derived from human stem cells. While progress is rapid and impressive in the beta cell replacement field, these approaches are expensive, limited by donor organ availability and will therefore not likely become available to the hundreds of millions of people around the world with diabetes. Since the large majority of people with diabetes have some residual beta cells in their pancreata, an alternate approach to reversing diabetes would be developing pharmacologic approaches to induce these residual beta cells to regenerate and expand in a way that also permits normal function. Unfortunately, despite the broad availability multiple classes of diabetes drugs in the current diabetes armamentarium, none has the ability to induce regeneration or expansion of human beta cells. Development of such drugs would be transformative for diabetes care around the world. This picture has begun to change. Over the past half-decade, a novel class of beta cell regenerative small molecules has emerged: the DYRK1A inhibitors. Their emergence has tremendous potential, but many areas of uncertainty and challenge remain. In this review, we summarize the accomplishments in the world of beta cell regenerative drug development and summarize areas in which most experts would agree. We also outline and summarize areas of disagreement or lack of unanimity, of controversy in the field, of obstacles to beta cell regeneration, and of challenges that will need to be overcome in order to establish human beta cell regenerative drug therapeutics as a clinically viable class of diabetes drugs.